Variabilidade espacial de perdas de solo, do potencial natural e risco de erosão em áreas intensamente cultivadas - De Mello, Gláucia [UNESP]; Bueno, Célia R. P. [UNESP]; Pereira, Gener T. [UNESP] (FapUNIFESP (SciELO), 2006)
The objective of this work was to identify the spatial variability of the natural erosion potential, soil loss and erosion risk in two intensely cultivated areas, in order to assess the erosion occurrence patterns. The soil of the area located at Monte Alto, São Paulo state, was classified as Paleudalf (PVA) with moderately slope, with different managements. The soil of the area located at Jaboticabal, São Paulo state, was classified as Haplortox(LV) with gentle slope and cultivated with sugarcane. A irregular grid was imposed on the experimental areas. Soil samples were obtained from 0-0.2 m depth at each grid point: 88 samples in Monte Alto area (1465 ha) and 128 samples at Jaboticabal area (2597 ha). In order to obtain the values of the studied variables USLE was applied at each grid point. Descriptive statistics were calculated, and geoestatistical analyses were performed for defining semivariograms. Kriging techniques to develop map showing spatial patterns in variability of selected soil attributes were used. All variables showed spatial dependence. The PVA soil showed higher erosion risk due to the slope and atual management compared to the soil LV.
Spatial variability of the soil loss, natural potential and erosion risk in intensively cultivated areas
Keywords: Geoestatistics; Soil conservation; Soil map; USLE (Universal Soil Loss Equation)